Remarks upon Capt. Middleton's defence [electronic resource] : wherein his conduct during his late voyage for discovering a passage from Hudson's-Bay to the South-Sea is impartially examin'd, his neglects and omissions in that affair fully pro'd, the falsities and evasions in his defence expos'd, the errors of his charts laid open and his accounts of currents, streights, and rivers, confuted, whereby it will appear, with the highest probability, that there is such a passage as he went in search of : with an appendix of original papers and a map of the in-land and sea-coast of North-America in and about Hudson's Bay - Dobbs, Arthur, 1689-1765 (London : Printed by the author's appointment, and sold by Jacob Robinson ., 1744)
Electronic reproduction. Mode of access: Internet. 44